Cyclist aerodynamics through time: Better, faster, stronger - Malizia, F.; Blocken, B. (Journal of Wind Engineering and Industrial Aerodynamics, 2021)
The last decades have seen an increasing interest in cycling aerodynamics, with the design of more aerodynamic bicycles and wearable equipment such as helmets and skinsuits and the development and application of new cyclist positions. Moreover, a better understanding of the flow topology around a cyclist and of the aerodynamic interaction between cyclists and other cyclists and nearby vehicles has been gained. However, some knowledge - albeit mainly empirical - of the impact of aerodynamics on cycling performance was already known in late 1800s and early 1900s; as shown by the design of recumbent bicycles and aerodynamic fairings, the adoption of dropped cyclist positions and the organization of drafting races. The goal of this paper is to demonstrate the evolution of aerodynamic knowledge in cycling from the early days to the most recent state-of-the-art to efficiently drive future studies. Therefore, this paper provides a comprehensive review of the history and state-of-the-art in cyclist aerodynamics, focused on three aspects: (i) cycling flow topology and the wind influence; (ii) the aerodynamics of a single cyclist and his/her wearable components; and (iii) the aerodynamic interaction between a cyclist and other cyclists or nearby vehicles. Finally, some future perspectives about cyclist aerodynamics are provided.